Is Sub-Saharan Africa likely to yield demographic dividends in the 21st century? - Ngcongo, Nokukhanya (Graduate School of Business (GSB), 2024)
Sub-Saharan Africa (SSA) has been undergoing an increase in population, which has seen the region grow from 0.55 billion people in 1990 to 1.17 billion in 2021. By 2100 it is estimated that SSA will be accounting for 35 percent of the global population - up from 14 percent in 2019. This increase in population will result in an increase of the working age population, which in turn presents an opportunity to yield demographic dividends. Demographic dividends occurs when there is a substantial increase in economic growth due to an increase in working age population. This dissertation examines the impact of the increase in (i) working age population (ii) female working age population on economic growth. In addition, the study also examines the impact of human capital and savings on economic growth, as they are co-determinants of demographic dividends. The study uses dynamic panel data from 40 countries within the region over a period of 2000 to 2018, using GDP per capita to represent economic growth while controlling for natural resources, rule of law, technology and trade openness. The Pooled Mean Group (PMG) and the two-step difference Generalised Method of Moments (GMM) were used to predict the relationship amongst the dependent and independent variables. The main findings of the study using PMG estimation are that: (i) there is a negative statistically significant relationship amongst working age population, female working age population and GDP per capita, due to the unproductive labour impact and low income levels; (ii) there is a positive and statistically significant relationship amongst human capital (education and health) and GDP per capita; and (iii) savings has a positive and statistically significant relationship with GDP per capita, however the impact is minimal due to the high dependency ratio and the population still consuming a significant portion of their income. Further to the PMG estimation, the GMM estimation was applied on the panel data to evaluate the validity and robustness of the PMG empirical results. The GMM estimator observed a similar directional relationship as the PMG amongst the main variables. An analysis was also performed on sub-regional data, which showed similar observations to the macro results of SSA. The empirical results from this study clearly highlight the significance of improving human capital in the region, as this will advance labour supply in terms of productivity, innovation and technological enhancements, which will have a positive impact on GDP per capita and increase the earning potential of the population. This will then become a catalyst for improved savings and wealth accumulation